2018
DOI: 10.1111/1477-9552.12298
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Framing and Monetary Incentives in Field Experiments on Risk Preferences: Evidence from German Farmers

Abstract: Recent studies cast doubt on the ability of abstract experiments to predict decision-making in the field. Thus, scholars have argued for more 'realism' by introducing context to field experiments. Yet, such realism may work against the induced values of monetary incentives in economic experiments. It is an open question whether contextual framing works best with or without inducing values, through methods such as the use of monetary incentives. Using a sample of 146 German farmers, we compare experimentally th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Sanou, Liverpool-Tasie, and Shupp (2018) reached the same conclusion using an incentivized CE MPL within a contextualized field experiment that was conducted in Nigeria. In contrast, Rommel et al (2019) found that insurance choices were not correlated with risk preferences elicited via contextualized and noncontextualized framings of the MPL. In this paper, a contextualized CE MPL was used.…”
Section: Eliciting Risk Preferencesmentioning
confidence: 64%
See 1 more Smart Citation
“…Sanou, Liverpool-Tasie, and Shupp (2018) reached the same conclusion using an incentivized CE MPL within a contextualized field experiment that was conducted in Nigeria. In contrast, Rommel et al (2019) found that insurance choices were not correlated with risk preferences elicited via contextualized and noncontextualized framings of the MPL. In this paper, a contextualized CE MPL was used.…”
Section: Eliciting Risk Preferencesmentioning
confidence: 64%
“…Recently, few studies attempted the use of contextualized field experiments. Results on the effect of contextual framing on external validity of elicited preferences and farmers' understanding of experimental tasks and instructions are mixed (e.g., Rommel, Hermann, & Musshoff, 2017;Rommel, Hermann, Muller, & Musshoff, 2019). This suggests that the use of contextualized field experiments needs further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine the sample size requirements for each game, we conducted power analyses to obtain the optimal number of observations required for each game [ 63 , 66 , 68 75 ]. The a priori power analysis required a minimum of 164 subjects for paired games: Dictator game, Trust game, Double Auction, and Ultimatum game, (82 per role) and a minimum of 82 subjects for the Public goods game and for the individual games: Holt and Laury, Eckel and Grossman, and Cheating game to have 80% power and a medium effect size (Cohen’s D = 0.50) using G*Power.…”
Section: Experimental Designmentioning
confidence: 99%
“…An explorative study with Swedish farmers (Labajova, 2018) and exploratory interviews with German farmers guided the experimental design, specifically with respect to framing the decision in a familiar context to enhance external validity and comprehension (cf. Meraner et al, 2018;Rommel et al, 2017Rommel et al, , 2019. In an artifactual field experiment, non-student subjects are recruited for participation in an experiment which may help to identify differences in behavior across subject pools and the sensitivity of behavior to context (Cason and Wu, 2019;Rahwan et al, 2019).…”
Section: Experimental Design To Measure Illusion Of Controlmentioning
confidence: 99%